Predictive factors for delayed hyponatremia after transsphenoidal surgery in patients with pituitary adenomas. Issue 1 (7th January 2022) - Lin, Kunzhe; Lu, Lingling; Pei, Zhijie; Mu, Shuwen; Huang, Shaokuan; Wang, Shousen
Abstract : Objective: The aim of this study was to evaluate the incidence and duration of delayed hyponatremia and to assess the factors influencing the development of delayed hyponatremia after transsphenoidal surgery (TSS) in pituitary adenomas. Methods: We retrospectively analyzed the clinical data of patients with pituitary adenoma who underwent TSS. Univariable and multivariable statistics were carried out to identify factors independently associated with the occurrence of delayed hyponatremia. Results: Of the 285 patients with pituitary adenoma who underwent microscopic TSS, 44 (15.4%) developed postoperative-delayed hyponatremia and 241 (84.6%) did not. The onset of delayed hyponatremia occurred an average of 5.84 days post-surgery and persisted for an average of 5.36 days. Logistic regression analysis showed the highest risk of delayed hyponatremia in patients with significant change in tumor cavity height (odds ratio (OR), 1.158; 95% CI, 1.062, 1.262; P = 0.001), preoperative hypothalamus–pituitary–thyroid axis hypofunction (OR, 3.112; 95% CI, 1.481, 6.539; P = 0.003), and significant difference in blood sodium levels before and 2 days after TSS (OR, 1.101; 95% CI, 1.005, 1.206; P = 0.039). Conclusions: Preoperative hypothyroidism, difference in blood sodium levels before and 2 days after TSS, and the change in tumor cavity height after TSS played important roles in predicting postoperative-delayed hyponatremia onset in patients with pituitary adenomas.